Mecanismos determinantes da agressividade intercolonial em cupim - Ferreira, Dinamarta Virginio (2018)
Aggressive behaviour can ensure animals access to local resources contributing to fitness increment. To reduce constant costs in the defence of territories, individuals could save energy with conflicts avoiding aggression with neighbour (Dear Enemy Hypothesis). This reduction in aggressiveness can be determined by the increase of encounters and consequently odor habituation among neighbours. Social insects have an efficient recognition system that guarantees social cohesion and protection against intruders in their colonies and territories. Here, we analysed the effect of distance among colonies and resource availability on the aggression level and responses to chemical cues of Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae). We also tested if this pattern could be promoted by previous exposure to intercolonial odors and the type of resource consumed. Manipulation of resource offer was conducted in the field during three months, where nests with different distances were kept without addition of baits (control), with addition of three or 16 sugarcane baits/nest. Bioassays of aggressiveness, linear and Y-shaped trail following bioassays were carried out with all pairwise combinations of colonies in each treatment. The effect of previous exposure to intercolonial odor and the consumption of similar resources on aggressive behavior and choice of intercolonial cues was tested in laboratory conditions. Our results showed individuals from colonies with 0 and 3 baits/nest showed a higher number of fighting with neighbours than those from non-neighbours colonies. Termite workers from colonies without baits (control) followed shorter distance in the linear trails compared to those from colonies with addition of baits. Intercolonial aggressiveness was not affected by previous exposure to intercolonial odor and neither by the consumption of similar resources. However, individuals previously exposed to intercolonial odor were more attracted to these odors than individuals who had no prior exposure. In addition, individuals from colonies of N. aff. coxipoensis that use similar resources increased the number of vibration than individuals who consumed different food resources. We concluded that the response of intercolonial aggressiveness in N. aff. coxipoensis seems to be resource-dependent. These results may contribute to the comprehension of the use of space by N. aff. coxipoensis and could be useful to explain patterns of termite species co-occurrence at natural conditions.